Mobilidade do capital, atores de veto e redistribuiç\~ao na América Latina durante a virada à esquerda - Fabiano Guilherme Mendes Santos; Acir Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This study explains the intensity of redistributive policies of Latin American leftist governments during the so-called "left turn" in the region. Based on theoretical models that analyze the implications of inequality in democracies with different economic and institutional structures, it argues that the left's redistributive policies were more intense in countries where capital has low mobility and the legislature was not a veto player. This explanation is supported by evidence from econometric models of a proxy measure of the intensity of redistributive policy, based on data from twenty leftist governments from eleven Latin American countries, during the 2000-2014 period.
Keywords: E6; Y8; 330; redistribution; capital mobility; veto player; Latin America